Symbolic policing: situating targeted police operations/‘crackdowns’ on street-level drug markets - Coomber, Ross (Policing and society, 2019)
The policing of local drug markets in England often takes the form of specific, high-profile, crackdown operations which themselves are mostly a generic, periodic response to particular criminality. Drawing on Innes’ (2004) concept of ‘control signals’ and Edelman’s (1985) notion of ‘symbolic policy’, we argue that ‘symbolic policing’ relates to activity that is principally about achieving symbolic aims - ‘being seen to be doing something’ rather than preventing or solving crime. This article, focusing on police crackdown operations on heroin and crack cocaine ‘dealers’ in three English urban areas, considers the meanings of such operations, how they work, and in relation to local suppliers suggests they may in fact have counterproductive enforcement outcomes whilst still achieving symbolic objectives. It is concluded that generic crackdown operations at the level of local drug markets are unhelpfully insensitive to local conditions and that, in certain circumstances, they can be antithetical to more considered enforcement and public health aims.